A Real-Time Visible Light Communication System on Chip Design for High Speed Wireless Communication - Trio Adiono (Proceeding of the Electrical Engineering Computer Science and Informatics, 2019)
The increasing demand of wireless communication bandwidth due to advancement of IoT and smartphone technology, requires the new wireless communication technology that can provide high speed wireless communication. The Visible Light Communication (VLC) has been proven can provide multi gigabit wireless communication throughput using unlicensed visible light spectrum. Therefore, VLC is a promising technology to solve bandwidth limitation problem. In order to achieve high speed throughput, VLC signal processing has to be implemented using Application Specific Integrated Circuits (ASICs) technology. In this research, we develop a baseband processor architecture for VLC application. We use System on Chip (SoC) design approach to reduce design time and easy system integration to various applications. In order to increase spectrum efficiency, we utilize OFDM modulation scheme. Several OFDM processing blocks, such as synchronizer, FFT/IFFT, modulator, demodulator, are designed in the system. The real-time system performance is verified in FPGA based system prototyping. The design includes optical wireless front end module, baseband processing and network layer. The developed prototype shows a real-time performance for high speed internet access.